Nutritional trends among children under the age of five in Zambia: A repeated cross sectional analysis using Zambia demographic health survey (2002–2018) - Namukolo Mukubesa; Leah Kamulaza; Mutale Sampa; Atupele Chisiza; Nasilele Amatende; Hope Sabao; Wilbroad Mutale (PLoS ONE, 2026)
Childhood undernutrition, manifested as stunting, wasting, and underweight, remains a major public health challenge, particularly in low- and middle-income countries. In Zambia, the burden of undernutrition remains persistently high despite ongoing interventions. This study analyzed trends and determinants of nutritional status among children under five years using data from the Zambia Demographic and Health Survey (ZDHS) conducted in 2002, 2007, 2013–14, and 2018. The analysis assessed the prevalence of stunting, underweight, and wasting in children aged 0–59 months, using mean Z-scores and standard deviations. Logistic regression models were applied to identify key socio-demographic and health-related risk factors, with analyses performed in Python, accounting for survey design and weights. Findings revealed a notable decline in malnutrition: stunting dropped from 45.6% in 2002 to 34.7% in 2018; underweight from 27.3% to 11.6%; while wasting remained stable at approximately 4%. Severe stunting and underweight also decreased significantly, whereas severe wasting fluctuated. Prevalence rates were higher when excluding children under six months (left-truncated data), suggesting possible protection from early infancy due to exclusive breastfeeding. Key predictors of malnutrition included low birth weight, poverty, regional disparities, and diarrheal episodes. Despite progress, stunting remains a pressing concern. The higher rates observed in older infants point to the need for strengthened interventions targeting the postnatal period. Enhancing maternal and child health services, improving nutrition programs, and addressing poverty are critical to sustaining reductions in childhood malnutrition.